2012
DOI: 10.1523/jneurosci.0509-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Functional Parcellation of the Lateral Mesencephalus

Abstract: The mesencephalic locomotor region (MLR), which includes the pedunculopontine nucleus (PPN) and the cuneiform nucleus (CN), has been recently identified as a key structure for locomotion and gait control in mammals. However, the function and the precise anatomy of the MLR remain unclear in humans. To study the lateral mesencephalus, we used fMRI in 15 right-handed healthy volunteers performing two tasks: imagine walking in a hallway and imagine an object moving along the same hallway. Both tasks were performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 49 publications
2
38
0
Order By: Relevance
“…EMG recordings confirmed that the motor activations seen during MI did not result from actual movements. Such motor activations during gait imagery have already been reported [Karachi et al, ; Malouin et al, ; Miyai et al, ; Sacco et al, ; van der Meulen et al, ], and could thus be specifically related to the use of kinesthetic MI.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…EMG recordings confirmed that the motor activations seen during MI did not result from actual movements. Such motor activations during gait imagery have already been reported [Karachi et al, ; Malouin et al, ; Miyai et al, ; Sacco et al, ; van der Meulen et al, ], and could thus be specifically related to the use of kinesthetic MI.…”
Section: Discussionmentioning
confidence: 64%
“…Because of a priori hypotheses regarding the involvement of cortical (mainly in frontal, premotor, and motor areas), subcortical (thalamus and BG), and brainstem regions, an uncorrected threshold (P < 0.001) for multiple comparisons across the whole brain (Z-scores > 3.10) was applied at the voxel level using flexible factorial design with the linear contrasts defined above. This level of significance has been used in previous neuroimaging studies having used MI method with a similar, or higher, number of subjects [e.g., Guillot et al, 2009;Jahn et al, 2004;Karachi et al, 2010Karachi et al, , 2012Malouin et al, 2003;Samuel et al, 2001;Thobois et al, 2000Thobois et al, , 2002van der Meulen et al, 2014]. Only voxels exceeding a threshold of a P-value < 0.001 uncorrected and clusters of a minimum of 20 contiguous voxels were considered significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Allali et al, 2014, Bakker et al, 2008, Cremers et al, 2012, Godde and Voelcker-Rehage, 2010, Iseki et al, 2008, Hanakawa et al, 1999, Jaeger et al, 2014, Jaeger et al, 2016, Jahn et al, 2008, Jahn et al, 2004, Karachi et al, 2012, la Fougere et al, 2010, Martinez et al, 2016, van der Meulen et al, 2014, Wagner et al, 2008, Wutte et al, 2012, Zwergal et al, 2012) The ALE significance map (p<0.01, uncorrected) included 6,790 voxels (54,320 mm 3 ) distributed across the brain with the largest clusters in the anterior, superior, medial cerebellum, medial motor cortices, and bilateral anterior insular cortices (Supplemental Figure 1). Eighty-one out of 296 parcels (27%) from the BnS atlas had ≥15 voxels (120 mm 3 ) with gait-related ALE p<0.01.…”
Section: Resultsmentioning
confidence: 99%
“…However, besides affecting motor performance, PPTg-DBS has remarkable consequences on non-motor functions, in particular in regulating REM sleep and arousal mechanisms [2][3][4]6,27].…”
Section: Introductionmentioning
confidence: 99%